Construções dialógicas em charges que tematizam a transposição do rio São Francisco - Menezes, Ana Karla Alves de (2018)
According to the perspective of the Dialogical Theory of Language, represented by Bakhtin and his Circle, as well as by other authors’ studies like Brait (2008), Faraco (2003), Sobral (2009), among others, this study aimed to analyze the dialogical constructions in the discursive genre cartoon in the enunciative event Transposition of the São Francisco River. Regarding about the specific purposes, we point out: a) to establish the dialogical relations among the voices present in the cartoons’ speeches; b) to understand the different forms of representation for the theme Transposition of the São Francisco River according to the enunciators’ point of view in the cartoons and c) to compare the game of words present in the cartoons which refer to the Transposition of the São Francisco River. This research is based on the Dialogical Theory of Language (DTL), specifically on dialogical readings of cartoons. It is considered an exploratory-descriptive study, whose methodological approach used was the dialogical one, comparing the texts in the event and the answers that one gives to the others, and presenting as the statements materialize, the social interaction and their answers, as the texts cannot be analyzed without considering them to be utterances-answers. The selected corpus consists in 06 (six) cartoons, from December of 2016 to March of 2017, hosted in Google Images. From the analysis of this study, we find out that the cartoons keep the dialogue with other genres of discourse and with other discourses. Another point relevant is that not only linguistic utterances are used but also the imaginary elements that make up the utterance as a whole and alter their meanings. The representation of another illustration present or an uttered enunciative (intertextualities) not only change meanings but also build several others. There fore, the cartoons analyzed show the dialogical representations that denounce or reinforce the negative understandings about the event Transposition of the São Francisco River, according to the aspects of the genre analyzed.